A METHOD FOR GENERATING HIGH-RESOLUTION VIRTUAL OUTCROP MODELS AT THE LUSITANIAN BASIN, WEST OF PORTUGAL (Anais do Salão Inovação, Ensino, Pesquisa e Extensão, 2020)
Virtual Outcrop Models (VOM) are digital and 3D representations of rock exposures at the Earths surface. Traditionally, these models have been built using the technology of Light Detection and Ranging (LiDAR). A new way to construct these models is the Structure from Motion (SfM) algorithm. SfM is used to generate 3D models from raster images (2D) based on parallax effect. SfM algorithms use photographys acquired from a terrestrial or aerial digital camera. The first one depends on a stable place to set the camera and the manual configuration of the angles and positions used to capture the scene. The second can be obtained by airplanes or Unmanned Aerial Vehicle (UAV). The resolution of a VOM depends in a few parameters, as the photo resolution (camera and object distance), the overlap rate between the photos and by the computer configuration used during the processing. Aiming the desired resolution along all the study area, its important to maintain the calculated setting during all acquisition flights. On targets placed in a map view this task can be done easily. On geological targets, rarely the object of study is placed this way. Due to this problem, this work proposes a new semi-autonomous way to acquire data, with UAV, aiming to produce high-resolution VOM. The study area corresponds of exposed rocks from a Jurassic succession situated at Lusitanian Basin, west coast of Portugal. Two main steps were followed to acquire aerial photographs of the area. The first one was focused on the construction of a low-resolution digital elevation model (DEM), using elevation information based on Shuttle Radar Topography Mission (SRTM). All data obtained at the first stage was then processed to construct a DEM with higher resolution compared with the SRTM. Using the results of the previous process as a control for autonomous flights in lower altitude, it was planned flights with 20m height. The data obtained with this second flight campaign was then processed to generate high resolution VOMs. The low-resolution models obtained an average resolution of 2 cm/pix, produced a DEM with an average resolution of 8 cm/pix. Models produced with photos obtained at the second flight campaign resulted in an average resolution of 8 mm/pix, DEMs with resolutions next to 3 cm/pix. Using this method for data acquisition made possible to solve the problem of low continuity of flight settings during campaigns and making possible the construction high resolution VOMs.